Influência do tamanho de parcelas experimentais na seleção de progênies de E. camaldulensis Dehnh - De Medeiros Silva, William [UNESP]; De Moraes, Mario Luiz Teixeira [UNESP]; Pupin, Silvelise- [UNESP]; Da Silva, Janete Motta [UNESP]; Sebbenn, Alexandre Magno; Pavan, Bruno Ettore [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2016)
In the choice of the size plots numerous factors must be considered in order to increase the efficiency of its selection, with the lowest operating cost. This work aimed to study the influence of two sizes plots in E. camaldulensis progeny tests for the variables stem shape, diameter at breast height, total height of the tree and total volume of the tree. EXP 1 and EXP 2 were implanted in a randomized block design, with 133 progenies and spacing of 3.0 mx 1.8 m. The EXP 1 set up five plants per plot and four replications and EXP 2 used a plant per plots and 20 repetitions. Estimates of variance components and genetic parameters were obtained using the REML / BLUP method. Coefficient of genotypic variation among progenies was similar in both experiments to stem shape and superior to the diameter at breast height, total height in EXP 2. For the four traits, heritability average level of progeny was higher in EXP 2, indicating greater efficiency in the genetic control at average progenies level. Experiment with one plant per plot offered higher gain with progenies selection, indicating favor on this design for superior individuals in general. The adoption of experiments with one plant per parcel together with the large number of replication is recommended for the Eucalyptus camaldulensis progeny tests.
Influence of the size plots in the selection of progenies of the Eucalyptus camaldulensis Dehnh
Keywords: Experimental design; Progeny test; REML / BLUP